WILLIAMSON, RODNEY Y DE DIEGO, FERNANDO (2005) Verbo e Imagen en la Telenovela mexicana (Revista Latinoamericana de Estudios del Discurso, 2020)
WILLIAMSON, RODNEY Y DE DIEGO, FERNANDO (2005) Verbo e Imagen en la Telenovela mexicana. Ottawa: LEGAS. 347 pp. IBSN: 1- 894508- 57-2.